Sportens egen domstol: Hot mot idrottarnas rätt till en rättvis rättegång? - Analys av The Court of Arbitration for Sport i förhållande till art. 6.1 EKMR - Hedberg,Jacob (2024)
The Court of Arbitration for Sport (CAS) is a global arbitration court which has ruled in sports law since its establishment in 1981. The arbitration court is the main court in sport disputes and acts as the last resort where subjects of sport can appeal decisions from different sport bodies to which they are bound and that includes an arbitration clause to CAS in the relevant statute. Although panels of CAS which accommodates rulings possesses certain competence in sports law in contrast to judges of a state court, the system is far from perfect. One aspect that has been subject to criticism and discussion is whether CAS is compatible with art. 6 of The Europa Convention of Human rights (ECHR) which regulates the right to a fair trial. To examine whether CAS is compatible with art.6 ECHR has been the main purpose of the essay. This purpose has been accommodated trough analyzing CAS own regulation in comparison with the jurisprudence of The European Court of Justice and articles with a critical perspective on CAS. The main judgement regarding CAS by the European Court of Justice has also been analyzed. The main method that has been applied is legal dogmatic method through analyzing applicable law with a critical perspective on the Court’s jurisprudence and CAS own regulations. CAS has mainly been criticized for its close ties with the sport bodies through the closed list of arbitrators which has been chosen mostly by persons representing the sport bodies trough the International Council of Arbitration for Sport (ICAS) which is the body that regulates and runs CAS. The rights which have been subject to analysis and investigation in this essay surrounds art. 6.1 ECHR which states inter alia the right to an independent and impartial tribunal established by law. The legality of forced arbitration has also been assessed. If an arbitration is considered forced, the rights in art. 6 cannot be waived. The assessment regarding whether a court is impartial contains both a subjective and objective aspect. The concept of an independent court contains a prohibition for a court to be subject to outside pressure. The European Court of Justice took a stand on the questions a few years ago in the judgement of Mutu and Pechstein v. Switzerland which dealt with inter alia the discussion regarding whether the arbitration of CAS should be defined as forced arbitration and if the arbitration court because of its close connection with the sport bodies can still be regarded as an impartial and independent tribunal established law. The Court qualified the arbitration as forced but that CAS is compatible with art. 6 ECHR although it acknowledged that the sport bodies have a certain influence on the arbitration court but not in a way that would affect the actual dispute. The Court therefore based its judgement only on the subjective part of the assessment regarding if a court is impartial. The court also omitted to state their view on certain aspects regarding removal of judges without justification by ICAS as well as applying the presumption that a court is impartial if its objectively perceived as impartial. The court therefore departed from its jurisprudence and as stated in this essay the judgement could be regarded as incomplete and unconvincing. The conclusion is therefore made that CAS has certain rules in its code which makes it from an objective point of view perceived as partial and connected to the sport bodies which indicates a need for reforms, but it remains unclear whether there is actual interest in all disputes which split all athletes into one camp and all sport bodies into another which would if it were the case create problems regarding CAS impartiality and independence.
Keywords: Processrätt; Idrottsjuridik; Sports Law; Europakonventionen; EKMR; ECHR; arbitration law; skiljemannarätt